Relevance of Religious Value and Customer Value inIncreasing Costumer Comsumption and Trust in ThePandemic Covid 19 Condition - Deddy Ahmad Fajar; Farah Nur Fauziah (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2021)
The Covid 19 pandemic has attacked the entire world in terms of health,economics and socio-politics. On the economic side, it is experienced by all countries inthe world. There was an explosion of unemployment caused by all sides of the economy toa halt. A study is needed to see the relevance of religious value and customer value withconsumer power and trust. This study aims to describe the relevance of religious valuesand customer value in increasing consumer power and customer confidence in theconditions of Covid 19. This research is included in library research, which examines datasourced from library materials. The results showed that there is a relevance betweenreligious value and customer value in increasing customer productivity and trust